A Study on Current Situations, Needs and Guidelines for Developing Budget Management of Schools Under the Sakon Nakhon Primary Education Service Area Office 1 - Chuanchailuek, Wattana; Khajornpanyapaisan, Komsan; Ngoipoothon, Rutchadaporn (Journal of Education Rajabhat Maha Sarakham University, 2024)
The aims of this study were: 1) to study current situations and desirable conditions of school budget management, 2) to study the needs of school budget management and 3) to study the guidelines for developing school budget management. The sample consisted of school administrators and teachers on duty of school budget management head, totally 184 people. The sample size was determined using the Krejcie and Morgan table through stratified random sampling. The key informants were 3 school administrators and 3 teachers on duty of school budget management head from the best practice schools. The research tools consisted of a current situation questionnaire with discriminatory power between 0.30-0.81 and reliability of 0.96, a desired condition questionnaire with discriminatory power between 0.31-0.93 and reliability of 0.97 and a semi-structured interview. The data analysis statistics included percentage, mean, standard deviation and Improved Needs Priority Index Value. The findings were as follows: 1) The current situations and desirable conditions of school budget management in overall were at high and the highest level, respectively, 2) The top 3 needs of school budget management were financial management, budget allocation and accounting management and 3) The guidelines for developing school budget management were 19 practical guidelines. The appropriateness and probability of the guidelines were indicated at the highest level.